The Influence Of Paylater Use And Lifestyle On Consumptive Behavior In Bandar Lampung City - Renna Ardiyanti; M. Oktaviannur (Cita konsultindo, 2024)
This article aims to find out whether the use of paylaters and lifestyle influence consumer behavior in the city of Bandar Lampung. The problem focuses on changes in the behavior of paylater users who are becoming more consumptive and prioritizing lifestyle. This research uses a quantitative approach with a sample of 100 respondents. In collecting data through questionnaires. The method for analyzing data uses multiple linear regression analysis via SPSS 29. The results of the research show that the use of paylater has a positive and significant influence on consumptive behavior as well as lifestyle giving a positive and significant influence on consumptive behavior. Simultaneously the use of paylaters and lifestyle provide a positive and significant influence on consumer behavior.